Molecular Pathogenesis of Ebola Viral Hemorrhagic Disease: An Update - Chang, Jae C. (Emerging Trends in Disease and Health Research Vol. 9, 2022)
Ebola viral hemorrhagic disease is rare, but is a serious thrombo-hemorrhagic disorder that can occur in Ebola viral sepsis. The demise of the patient occurs due to severe inflammation, multi-organ dysfunction syndrome and hemorrhage associated with a poorly defined coagulopathy. However, recent studies in COVID-19 pandemic have confirmed that viral sepsis including Ebola virus causes endothelial injury via complement activation that promotes inflammation and microthrombogenesis forming microthrombosis that leads to endotheliopathy-associated vascular microthrombotic disease (EA-VMTD). It commonly develops in the liver of Ebola infection (i.e., acute hepatic necrosis) and in the lungs of COVID-19 infection (i.e., acute respiratory distress syndrome). To address clinical and hematological features, a novel pathogenesis based on “two-activation theory of the endothelium” was proposed. Viral sepsis causes microthrombosis via ultra large on Willebrand factor (ULVWF) path of hemostasis in vivo following endothelial release of ULVWF/FVIII and recruitment of platelets. Endothelial injury promotes release of biomolecules from endothelial cells, which provokes various clinical syndromes including severe inflammation, consumptive thrombocytopenia, microangiopathic hemolytic anemia, and multiorgan dysfunction syndrome. In Ebola viral sepsis, activation of inflammatory pathway causes severe inflammation, but activation of microthrombotic pathway produces disseminated VMTD. The pathogenesis of Ebola viral disease is further complicated by hepatic coagulopathy initiated by acute hepatic necrosis, which results in “microthrombo-hemorrhagic syndrome” (erroneously called “disseminated intravascular coagulation” in the past) associated with thrombotic thrombocytopenic purpura (TTP)-like syndrome. The correct diagnostic term for the viral thrombo-hemorrhagic syndrome is “EA-VMTD with hepatic coagulopathy”.